The Social Stress Indicator (SSI) - Combrink, Herkulaas (PLOS ONE, 2025)
Social media shapes perceptions, influences emotions, and fuels anxieties, yet its true impact on social stress remains difficult to measure. This study introduces the Social Stress Indicator (SSI) as a computational tool for quantifying social stress in real time by integrating sentiment analysis (SA), subjectivity (SUB), and information seeking behavior (ISB). The data used was synthetic, and no-real world data was used to test the context. To validate SSI, it was compared to an expert-labeled Social Stress Score (SSS), which assesses sentiment negativity, anxiety expression, engagement, misinformation, and help-seeking behavior. Results show that SSI moderately aligns with SSS but underestimates stress levels, especially during high-intensity events. Bland-Altman analysis confirmed a negative bias, suggesting SSI struggles to capture extreme stress. However, causality tests indicate SSI has predictive power, making it a potential early warning system for stress-related trends. Despite its promise, SSI faces limitations in detecting misinformation surges, crisis-driven anxiety, and nuanced social interactions. This study demonstrates the feasibility of computationally tracking social stress at scale but highlights the need for refinements. Future improvements should enhance sensitivity to extreme stressors, incorporate adaptive thresholding, and integrate contextual signals like network effects and linguistic nuances. This research advances infodemic intelligence, with implications for mental health monitoring, policy-making, and digital governance.